Komparasi Ketimpangan Distribusi Pendapatan Dalam Perspektif Ekonomi Konvensional Dan Ekonomi Islam - Chalid, Fitria Idham; Zubaidah, Siti (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
Income distribution plays an important role in the economy in both conventional and Islamic economics. In conventional economics, income distribution often focuses on market efficiency, but this can lead to inequality and social disparities. In contrast, Islamic economics emphasizes the principles of justice, respect for the Shari'a, and equitable distribution of wealth, using instruments such as zakat, infaq, and waqf to reduce inequality and achieve social welfare. This study uses a literature review method, this study identifies the challenges faced in implementing both income distribution systems. The main challenges in conventional economics include economic inequality caused by unequal access to education and resources, while in Islamic economics, the challenges lie in the implementation of distribution mechanisms that are not yet optimal. This study concludes that although both face challenges, the Shari'a-based distribution system is more inclusive and oriented towards social welfare, making it a fairer alternative in the long run.